YAP/TAZ-mediated activation of serine metabolism and methylation regulation is critical for LKB1-deficient breast cancer progression. Issue 5 (24th October 2017) - Wu, Qi; Li, Juanjuan; Sun, Si; Chen, Xinyue; Zhang, Hanpu; Li, Bei; Sun, Shengrong
Abstract : The crucial interplay between metabolic remodeling and the epigenetics could contribute to promote cancer progression. A remarkable association within interaction, LKB1 has been reported, suggesting that the expression of key enzymes involving de novo serine synthesis and DNA methyltransferases like DNMT1 and DNMT3A increase LKB1-deficiency cells. However, the complex interactional link between metabolic remodeling and the epigenetics is still unclear. Hence, we focus on the relationship between YAP/TAZ and serine metabolism to control methylation of DNA or histone in breast cancer with LKB1 deficiency. We hypothesize that YAP/TAZ may have the function to activate key enzymes involving serine metabolism like PSPH and up-regulate the amino acid transporters to supply sources of serine synthesis through activation of C-MYC with TEAD1. Further, we speculate that YAP/TAZ in dependent of FOS may promote DNMT1 and subsequently mediate DNMT1–G9A complex involving serine metabolism and the methylation of DNA and histone. We hope that our study will stimulate further studies and a new targeted therapy and early medical intervention for YAP/TAZ could be a useful option for breast cancer cases complicated with LKB1 deficiency.